The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acschemneuro.0c00089
|View full text |Cite
|
Sign up to set email alerts
|

Brain Endothelial Cell-Derived Exosomes Induce Neuroplasticity in Rats with Ischemia/Reperfusion Injury

Abstract: Exosomes derived from the cerebral endothelial cells play essential roles in protecting neurons from hypoxia injury, but little is known regarding the biological effects and mechanisms of exosomes on brain plasticity. In this study, exosomes were isolated from rodent cerebral endothelial cells (bEnd.3 cells) by ultracentrifugation, either endothelial cell-derived exosomes (EC-Exo) or PBS was injected intraventricularly 2 h after the middle cerebral artery occlusion/reperfusion (MCAO/R) model surgery in the Exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“… 28 In the case of ischemia/hypoxia, exosomes derived from endothelial cells can suppress neuronal death, promote neural plasticity, and improve functional recovery. 29 In the current study, we found that exosomes released from IPASs were transmitted to neurons as shuttles carrying circSHOC2, which ameliorated ischemia-induced neuronal apoptosis, indicating that IPAS-EXO-mediated circSHOC2 transport may be sufficient to protect neurons from ischemia-induced damage.…”
Section: Discussionsupporting
confidence: 49%
“… 28 In the case of ischemia/hypoxia, exosomes derived from endothelial cells can suppress neuronal death, promote neural plasticity, and improve functional recovery. 29 In the current study, we found that exosomes released from IPASs were transmitted to neurons as shuttles carrying circSHOC2, which ameliorated ischemia-induced neuronal apoptosis, indicating that IPAS-EXO-mediated circSHOC2 transport may be sufficient to protect neurons from ischemia-induced damage.…”
Section: Discussionsupporting
confidence: 49%
“…In the past, most studies have focused on static parameters of gait (print area, maximal contact area, and stride length) (Domin et al, 2016;Fan et al, 2018;Hu et al, 2019). Few studies have focused on dynamic parameters (Gao et al, 2020). Our research highlights whole-body dynamic parameters (average speed, maximum variation, number of steps, swing) in gait analysis.…”
Section: Discussionmentioning
confidence: 89%
“…The cardioprotective effect was not observed when treated with EV depleted conditioned media. Increased axonal growth and upregulation of miRNA related to the regulation of Sema6A, Phosphatase and Tensin Homolog (PTEN), and RhoA was observed with rat cerebral EC-EVs in vitro (Zhang Y. et al, 2020). Vascular smooth muscle cells showed an increased vascular cell adhesion molecule 1 (VCAM1) expression and leukocyte adhesion when cultured with rat cerebral EC-EVs (Boyer et al, 2020).…”
Section: Biological Activities Of Ec-evsmentioning
confidence: 97%
“…Endothelial colony-forming cells (ECFC)-EVs inhibited apoptosis and reduced ischemic kidney injury in mice ( Vinas et al, 2018 ). Brain EC-EVs promoted motor function and Synapsin I expression in the cerebral artery occlusion model of rats ( Gao et al, 2020 ). EVs from HUVECs cultured in high glucose media restored wound healing of basal glucose cultured HUVECs compared to EVs from HUVECs cultured in basal media ( Saez et al, 2018 ).…”
Section: Endothelial Cell-evsmentioning
confidence: 99%